2016
DOI: 10.1039/c5gc01070e
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy thermosets from model mixtures of the lignin-to-vanillin process

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
96
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 40 publications
1
96
1
Order By: Relevance
“…Currently, over 1.1 million tons of lignin are generated annually by industry with only about 2% used to produce valuable chemicals, demonstrating the vastness of this underutilized resource . Depolymerized lignin has been shown to be a valuable source of substituted phenolics, namely, vanillin and other methoxyphenols, that are produced on industrial scales and can be functionalized into polymer precursors . The high aromatic ring content of lignin imparts rigidity and strength to the biopolymer network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, over 1.1 million tons of lignin are generated annually by industry with only about 2% used to produce valuable chemicals, demonstrating the vastness of this underutilized resource . Depolymerized lignin has been shown to be a valuable source of substituted phenolics, namely, vanillin and other methoxyphenols, that are produced on industrial scales and can be functionalized into polymer precursors . The high aromatic ring content of lignin imparts rigidity and strength to the biopolymer network.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Depolymerized lignin has been shown to be a valuable source of substituted phenolics, namely, vanillin and other methoxyphenols, that are produced on industrial scales and can be functionalized into polymer precursors. [3,18,19,[26][27][28][29][30][31][32][33][34] The high aromatic ring content of lignin imparts rigidity and strength to the biopolymer network. This same aromaticity is what makes monomer units derived from the depolymerization of lignin so valuable as polymer precursors.…”
mentioning
confidence: 99%
“…The monomer approach toward renewable based epoxy thermosets from lignin‐obtained phenols was already intensively investigated. Vanillin‐based epoxy thermosets were described in detail by Caillol and co‐workers . Recently, epoxy thermosets from glycidylated iso‐eugenol were presented .…”
Section: Introductionmentioning
confidence: 99%
“…Although the commercial application of bio‐based polymers can mitigate environmental impacts, it is important that any bio‐based polymer that is considered as a replacement for petroleum‐based counterparts (such as bisphenol A‐based polymers) exhibits similar properties, including good thermal stability, mechanical strength, processability and compatibility . Therefore, many efforts are currently underway to develop new bio‐based polymers with higher performance values as replacements for polymers currently derived from petroleum‐based feedstocks …”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, many efforts are currently underway to develop new bio-based polymers with higher performance values as replacements for polymers currently derived from petroleum-based feedstocks. [10][11][12][13][14][15][16] Advances in industrial biotechnology mean that an increasing number of chemicals are becoming available from renewable resources that can be used as substrates for the synthesis of bio-based polymers with improved properties. [17][18][19] For example, Hong et al have reported a water-soluble epoxy resin prepared from diglycidyl ethers of isosorbide and isosorbide diamine.…”
Section: Introductionmentioning
confidence: 99%